2015
DOI: 10.3171/2014.12.jns141288
|View full text |Cite
|
Sign up to set email alerts
|

Timing of deep vein thrombosis formation after aneurysmal subarachnoid hemorrhage

Abstract: OBJECT Deep vein thrombosis (DVT) is a common complication of aneurysmal subarachnoid hemorrhage (aSAH). The time period of greatest risk for developing DVT after aSAH is not currently known. aSAH induces a prothrombotic state, which may contribute to DVT formation. Using repeated ultrasound screening, the hypothesis that patients would be at greatest risk for developing DVT in the subacute post-rupture period was tested. METHODS One hundred ninety-eight patients with aSAH admitted to the Oregon Health & Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…Our study demonstrated no significant impact of the VTE bundle on the overall 12% incidence of VTE. This incidence is similar with the reported range noted in the literature for SAH population, typically ranging from 4.4% to 21% [1][2][3][4]9]. Furthermore, our study also identified three significant predictors of VTE -Caprini score, NSICU LOS, and the presence of baseline lung diseases.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study demonstrated no significant impact of the VTE bundle on the overall 12% incidence of VTE. This incidence is similar with the reported range noted in the literature for SAH population, typically ranging from 4.4% to 21% [1][2][3][4]9]. Furthermore, our study also identified three significant predictors of VTE -Caprini score, NSICU LOS, and the presence of baseline lung diseases.…”
Section: Discussionsupporting
confidence: 90%
“…Venous thromboembolism (VTE) remains a common morbidity in patients with subarachnoid hemorrhage (SAH). Past studies have reported the incidence of VTE ranging from 0% to as high as 24%, most occuring within the first two weeks following SAH [1,2]. The higher rate is often associated with the use lower-extremity surveillance ultrasonography, where higher rates of asymptomatic deep vein thrombosis were detected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IPC is the recommended VTE strategy in this population and should be started immediately upon admission (2). UFH should be initiated as well unless in cases of unsecured ruptured aneurysms expected to undergo surgery (19). This may be extrapolated for patients undergoing endovascular treatment but data are not clear yet on this matter.…”
Section: Resultsmentioning
confidence: 99%
“…Acute brain injury (ABI) patients (including acute traumatic brain injury, acute hemorrhagic stroke, acute ischemic stroke and acute aneurysmal subarachnoid hemorrhage patients) who are treated in the neurocritical care unit are at high risk for deep vein thrombosis (DVT) of the lower limb; the risk varies considerably from 17-40% with different diagnostic strategies [1][2][3][4]. Isolated distal deep vein thrombosis (IDDVT) of the lower limb, also known as calf DVT, refers to infrapopliteal vein DVT that does not extend to proximal veins [5].…”
Section: Introductionmentioning
confidence: 99%